2020
DOI: 10.1155/2020/7250287
|View full text |Cite
|
Sign up to set email alerts
|

The Late-Gestational Triglyceride to High-Density Lipoprotein Cholesterol Ratio Is Associated with Neonatal Macrosomia in Women without Diabetes Mellitus

Abstract: Objective. To investigate the associations between late-gestational dyslipidemia, expressed as the ratio between triglycerides (TGs) and high-density lipoprotein cholesterol (HDL), and the risk of macrosomia among nondiabetic pregnant women. Methods. In this case-control study, 171 pregnant women who delivered macrosomia newborns were recruited from a total of 1856 nondiabetic pregnant women who delivered a singleton, nonanomalous newborn. A total of 684 normal controls were one-to-four matched by age. Logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…We found birth weight was affected by abnormal TG levels of pregnant women, which agreed with the results of many studies [ 13 , 14 , 15 ]. In our study, the median levels of TG/HDL ratio were higher in LGA newborns, which agreed with the study that found the TG/HDL ratio showed an obvious dose-dependent relationship with the occurrence of macrosomia [ 16 ]. Consistent with our result, most studies had not found relationships between maternal serum TC and LDL levels and birth weight [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found birth weight was affected by abnormal TG levels of pregnant women, which agreed with the results of many studies [ 13 , 14 , 15 ]. In our study, the median levels of TG/HDL ratio were higher in LGA newborns, which agreed with the study that found the TG/HDL ratio showed an obvious dose-dependent relationship with the occurrence of macrosomia [ 16 ]. Consistent with our result, most studies had not found relationships between maternal serum TC and LDL levels and birth weight [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the median levels of TG/HDL ratio were higher in LGA newborns, which agreed with the study that found the TG/HDL ratio showed an obvious dose-dependent relationship with the occurrence of macrosomia [ 16 ]. Consistent with our result, most studies had not found relationships between maternal serum TC and LDL levels and birth weight [ 13 , 16 ]. Weight in early life was highly associated with weight and quality of life in children, adolescents and adults [ 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Paradoxically, multivari-ate logistic regression analysis showed that TG and HDL levels in elbow vein and umbilical cord blood were not significantly correlated with neonatal weight. Yu's report exhibited similar result that the serum TC and LDL-C levels were not significantly different of the macrosomia and control groups, but maternal TG/HDL levels were positively associated with neonatal weight [19]. However, maternal blood lipid levels during pregnancy significantly increased, and hyperlipidemia may participate in the circulation and metabolism of other nutrients, indirectly affecting the growth and development of the fetus [20].…”
Section: Discussionmentioning
confidence: 79%
“…Numerosos trabajos indican que los niveles de TG maternos sirven como predictores de la presencia de macrosomía, incluso en pacientes sin DM gestacional [31][32][33][34][35] , mientras que no sucede lo mismo con el colesterol. Recientemente, un trabajo reportó que la relación TG/colesterol total aumentada sería un condicionante para el desarrollo de macrosomía 36 .…”
Section: Discussionunclassified